Colombia : Review Under the Flexible Credit Line Arrangement--Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2012)
Colombia's very strong track record of macroeconomic policy management, underpinned by robust fiscal and monetary policy frameworks, has reduced vulnerabilities in recent years and helped weather the global financial crisis. The authorities' policy focus has shifted from supporting the recovery through appropriate countercyclical measures to rebuilding policy buffers through fiscal consolidation, the normalization of monetary policy, and a strengthening of the reserve position.